EFFECT OF SUGAR MIXTURES WITH DIFFERENT TYPES ON RHEOLOGICAL, PHYSICOCHEMICAL AND SENSORIAL QUALITY OF BISCUITS - Ozulku, G.; Ozcan, O.; Sener, D.; Atalay, A.; Karasu, S.; Sagdic, O. (PLAPIQUI(UNS-CONICET), 2022)
Sugar mixtures with different types are commonly used in biscuit formulation. This study investigates the mixture of crystal sucrose (CS) and fine sucrose (FS) for the quality of biscuits in terms of rheological, sensorial and physical properties. Mixture design approach was also used and the effect of model was significant for all dependent variables such as Tan d in rheological, hardness and spread ratio (SR) in physical, general acceptability in sensorial analysis. With CS decrement in the formulation, a reduction was observed for Tan d values. High level replacement of CS with FS (from 50% to 100%) causes dramatic increase in SR values of biscuits. Decreasing the replacement level of CS increased the hardness value of biscuits. The results of this study showed that the type of sucrose and the mixing ratio can significantly affect the physicochemical and sensory quality of the biscuit. The biscuit sample containing the 90% FS and 10% CS obtained the highest score for hardness, crispness, and general acceptability.
Keywords: Fine sucrose; crystal sucrose; biscuit; quality; mixture optimal design; rheology.; FLOUR; FUNCTIONALITY; BEHAVIOR; SUCROSE; COOKIE; CREEP; DOUGH; SNAP; Engineering